1984
DOI: 10.1159/000466192
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurization of C1 Inactivator in the Presence of Citrate Salts

Abstract: Conditions have been determined under which the C1 inactivator (C1-INA) can be pasteurized to reduce the risk of transfusion hepatitis associated with its use for replacement therapy in patients with genetic or acquired deficiencies. Recovery of 90% of the biological and immunological activity of a C1-INA concentrate was achieved following heat treatment for 10 h at 60 °C in the presence of 3 M potassium citrate. Crossed immunoelectrophoresis in heparinized agarose was used to demonstrate the ability of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Although precipitation problems interfered with the evaluation of citrate by the ANS technique, this compound has previously been shown to be effective in stabilizing antithrombin III [28,40,41], Cl inactivator [42] and a,-proteinase inhibitor [43], High concentrations of citrate also precipitate Cl inactivator, but prevent aggregation. In such cases, nonspe cific stabilizers which exert their influence via effects on solvent properties are likely to be more useful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although precipitation problems interfered with the evaluation of citrate by the ANS technique, this compound has previously been shown to be effective in stabilizing antithrombin III [28,40,41], Cl inactivator [42] and a,-proteinase inhibitor [43], High concentrations of citrate also precipitate Cl inactivator, but prevent aggregation. In such cases, nonspe cific stabilizers which exert their influence via effects on solvent properties are likely to be more useful.…”
Section: Discussionmentioning
confidence: 99%
“…A similar increase in opsonic activity has been reported to occur when purified Fn is incubated at 37 °C in the ab sence of stabilizers [49], A major reason for pasteurization of plasma derivatives is to decrease the inci dence of transmission of viral hepatitis. However, in vivo studies in chimpanzees are required to assess the effectiveness of hepa precipitation apparently does not interfere with, and is not required for, stabilization [42]. Citrate was therefore included in a group of seven protective compounds and mixtures which were then further tested for their ability to stabilize Fn during pasteuri zation for 10 h at 60 °C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-purity Cl-INA concentrate was prepared from the interme diate-purity concentrate by fractional precipitation with ammonium sulfate [31,32] Crossed immunoelectrophoresis (CIEP) was carried out as pre viously described [22], with antiserum to Cl-INA (Behring Diagnos tics) incorporated in the gel for the second dimension.…”
Section: Introductionmentioning
confidence: 99%
“…However, in later studies [20,21], the presence of sucrose was found to significantly reduce the virus inactivation rate during heat treatment. We reported that Cl-INA could with stand pasteurization treatment in the presence of 3 M potassium citrate [22], but a subsequent test using chim panzees revealed that under these conditions, the HBV was stabilized as well [23], Several investigators reported the use of dry heat for viral inactivation in human factor VIII [24][25][26] and factor IX [27], The dry-heat approach minimizes the risk of reinfection because it is performed in the final containers, …”
mentioning
confidence: 99%